Human rotavirus vaccine (Rotarix): focus on effectiveness and impact 6 years after first introduction in Africa. (August 2015) - O'Ryan, Miguel; Giaquinto, Carlo; Benninghoff, Bernd
<x xml:space="preserve">Abstract</x> A decade after licensure of the human rotavirus vaccine (HRV), a wealth of evidence supports a reduction of rotavirus (RV) gastroenteritis-associated mortality and hospitalizations following HRV inclusion in national immunization programs. Nevertheless, the majority of real-world data has been generated in high- or middle-income settings. Clinical efficacy trials previously indicated RV vaccine performance may be lower in less-developed countries compared with wealthier counterparts. Using recently published data from Africa, we examine the effectiveness and impact of HRV in resource-deprived areas, exploring whether vaccine performance differs by socioeconomic setting and the potential underlying factors. HRV vaccine effectiveness in early adopting African countries has proven to be similar or even superior to the efficacy results observed in pre-licensure studies.